PENGARUH PENAMBAHAN TEPUNG DAUN KELOR (Moringa Oleifera) TERHADAP PENAMPILAN PRODUKSI PUYUH FASE LAYER - Siwi Pretyka Sari; Alfan Setya Winurdana; Resti Yuliana Rahmawati (AVES: Jurnal Ilmu Peternakan, 2020)
The purpose of this study was to determine the effect of Moringa oliefera leaf meal on the performance of quail production including feed consumption and egg production. This study used a layer phase quail with premium strains. The number of quails used was 300 at 34 weeks age. This study used a completely randomized design (CRD) method. Consisting of 4 treatments and 5 replications, where each replication used 15 quails. The treatments used in the study were P0 as a control or without the addition of Moringa leaf flour, P1 1% Moringa leaf flour, P2 2% Moringa leaf flour, P3 3% Moringa leaf flour. This study concluded that the addition of Moringa leaf flour to the ration with a percentage of 3% significantly (P <0.05) increased the FCR value. Egg productivity had no significant effect (P> 0.05) on the addition of Moringa leaf meal with a percentage of 1%, 2%, and 3%.